ELV policy and management system in Malaysia: exploratory study of dynamics, rationale and opportunity through digitalised public services - Ahmad Nizam Che Kasim,; Mohd Shahidan Shaari,; Noorazeela Zainol Abidin,; Juraini Zainol Abidin,; Noor Azuan Hashim,; Altaf Hossain Molla,; Zambri Harun, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A sustainable end-of-life vehicle (ELV) management system requires a well-thought and well-designed process covering strategies, regulations, technologies, and future adaptive systems. Among others is the urgent need for feasible implementation of the integrated vehicle deregistration process, especially to kickstart the process for registered abandoned vehicles (approximately eight million units nationwide in 2018). In line with this aspiration, this study will explore the dynamics, rationale, and opportunity for public services to have a unified digitisation platform. This initiative will integrate networks of public (e.g., Ministry of Transport, Ministry of Housing and Local Government, Ministry of Environment and Water, Local councils, Road and Transportation Department, courts, Royal Malaysian Police), industry (e.g., authorised automotive treatment facilities (AATF), scrapyards) and other related parties. Those entities are critical to developing local ELV management system capacity to address current complex problems and achieve collective goals for the future automotive industry in Malaysia. Based on the Focus Group Discussion (FGD) outputs, literature survey, and relevant proposed frameworks, this study aims to enlighten policymakers on the necessity of having an integrated system in supporting various business, legal and administrative needs of the sustainable ELV Policy in Malaysia.